The genus Decaisnea in Vietnam, with a key to Vietnamese Lardizabalaceae - Anh, Tran Thi Phuong; Quang, Bui Hong; Nguyen, du Van; Nguyen, Khang Sinh; Sennikov, Alexander N.; Nuraliev, Maxim S. (Phytotaxa, 2025)
A historical and taxonomic overview of the genus Decaisnea (Lardizabalaceae) is provided, and the nomenclature of this generic name is reviewed and corrected. For each of its two currently accepted species, D. fargesii and D. insignis, the original material is revised, typification is clarified, and collection details of the type specimens are revealed. For both species, knowledge on their morphology, ecology and geographical distribution is updated. Evidence of the presence of Decaisnea in the flora of Vietnam is summarized; its presence in the country is confirmed for the first time by specimen revision. In Vietnam, the genus is shown to be represented by D. fargesii, which is known solely in Lao Cai Province, Hoang Lien National Park. The diversity of Lardizabalaceae in Vietnam is reviewed, and a key to the Vietnamese genera and species of the family is presented.